Persepsi Wisatawan terhadap Pengalaman Sensorik dalam Walking Tour di Kotagede - Astry Putri Dayanda Anabokay; Wiendu Nuryanti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Kotagede, one of the historic districts in Yogyakarta, boasts a rich cultural and architectural heritage that makes it a prominent destination for walking tours. Walking along its historic alleys, traditional buildings, bustling markets, and local life offers visitors an authentic cultural tourism experience. However, the current design of walking tours in Kotagede still tends to emphasize historical narratives and architectural visualization, leaving the multisensory potential of the area underutilized. This study aims to analyze how tourists perceive sensory experiences (visual, auditory, olfactory, gustatory, and tactile) during walking tours in Kotagede and to identify the most dominant elements that shape such experiences. The research employed a descriptive, qualitative approach, utilizing in-depth interviews, participatory observation, and documentation. The participants consisted of 32 tourists who had just completed a walking tour, selected through purposive sampling. The findings reveal that visual experience is the most dominant sensory element, particularly through traditional architecture and historic buildings. Auditory elements, such as birdsong and market activities, enrich the atmosphere, while tactile experiences with building materials provide authenticity and strengthen tourists' emotional connection with local history.Meanwhile, olfactory elements, such as the aroma of spices, incense, and aged wood, contribute to the overall ambiance, though occasionally disrupted by unpleasant odors from waste. Gustatory experiences are often encountered during tours of local culinary products, demonstrating strong potential as markers of cultural identity, although they are not yet fully integrated into the tour itinerary. These findings highlight a gap between Kotagede's multisensory potential and the existing design of the walking tour. Therefore, the development of more holistic sensory-based walking tours is necessary to enhance visitor satisfaction while reinforcing Kotagede’s cultural identity as a meaningful heritage destination.